Effectiveness of physical activity programs at worksites with respect to work-related outcomes - Proper, Karin I; Staal, Bart J; Hildebrandt, Vincent H; van der Beek, Allard J; van Mechelen, Willem (Scandinavian Journal of Work, Environment & Health, 2002)
This paper systematically reviews the literature on the effectiveness of physical activity programs at worksites with respect to work-related outcomes. A computerized literature search, a reference search, and a manual search of personal databases were performed using the following inclusion criteria: randomized controlled or controlled trial, working population, worksite intervention program to promote physical activity or physical fitness, and work-related outcomes. The study quality was evaluated using nine methodological criteria. Conclusions were based on a 5-level rating system of evidence. Eight studies (4 randomized controlled trials and 4 controlled trials) were identified, but their methodological quality was generally poor. The outcomes were absenteeism, job satisfaction, job stress, productivity, and employee turnover. The evidence of an effect was limited for absenteeism, inconclusive for job satisfaction, job stress and employee turnover, and nil for productivity. The scientific evidence on the effectiveness of physical activity programs at worksites is still limited. Because of the few high-quality randomized controlled trials, it is strongly suggested that this type of study be carried out. Future randomized controlled trials should pay special attention to the description of randomization, inclusion criteria, compliance, and analyses according to intention to treat.
Keywords: absenteeism; intervention study; physical activity program; physical fitness; review; review literature; systematic review; work-related outcome; workplace; worksite